Conceptualizing and exploring the unethical ProTeam behaviour in team sports - Shukla, Y.; Kushwaha, A.; Vigneashwaran, K. (Sport in Society: Cultures, Commerce, Media, Politics, 2025)
Unethical pro-team behaviour (UPTB) in sports constitutes actions by one or more team members aimed at gaining an advantage in the game, even at the expense of violating established social and ethical norms. This study aims to conceptualize and explore the UPTB in team sports. To do so, we analyse the Sandpapergate scandal, a notable scandal occurred in March 2018, when three prominent Australian cricketers were caught in misconduct involving the use of sandpaper to alter the condition of cricket ball during a test match against South Africa. The study draws on a diverse array of archival sources, including official records, newspaper accounts, social media discussions, and statements from the players involved in instances of UPTB. By shedding light on the antecedents and consequences of UPTB within the context of team sports, this study contributes to the understanding of the ethical challenges that athletes and sports organizations are facing. Furthermore, the findings of this study have the potential to develop strategies and interventions aimed at promoting a culture of integrity and fair play in sports.